The power of money in John Steinbeck’s Of Mice and Men: An Alvin Toffler perspective - Eka Harisma W; Nina Sulistyowati (LITERA, 2026)
Of Mice and Men is one of John Steinbeck novellas that describe the situation and condition of the great depression of American in 1930s. The novel portrays the lives of working-class men, particularly the main characters George, Lennie, and Curley. This study aims to explore the power of money in Of Mice and Men by employing an extrinsic approach that connects literary analysis with social thought, particularly Alvin Toffler’s theory of power dynamics. This research uses a qualitative descriptive method within the field of literary studies. The data are collected from the novel Of Mice and Men as the primary source, focusing on dialogues, narrative descriptions, and character interactions related to economic conditions. Data collection is conducted through close reading and note-taking techniques. Furthermore, the data are analyzed using an interpretative method by applying Toffler’s theory of power to identify how money functions as a source of power, control, and inequality within the story. By examining the characters' economic struggles and aspirations, this study reveals how wealth, as represented by money, shapes relationships, opportunities, and social hierarchies. Using Toffler's perspective, this study analyzes the depiction of economic dependency and powerlessness during the Great Depression. The findings show that money functions in three significant ways: (1) as a source of hope for laboring characters, (2) as a tool of control and domination exercised by capital owners over workers, and (3) as a symbol of social and economic inequality.